Rural Development Efforts In Improving Quality of life for rural women breadwinners in Ashmoun District Villages, Monofia Governorate - Elkholy, Amany Said Abdelhamed; Ibrahim, Eman Mostafa (Journal of Humanities & Social Sciences, 2022)
The research aimed to identify the levels of quality of life for the breadwinner rural woman, The extent of benefiting from development efforts, Identify the problems they face, Determining the relationship between the quality of life of breadwinner rural woman and some of her characteristics, Identifying the obstacles to rural women breadwinners benefiting from development efforts and their proposals to reduce them. the systematic random sample184 Rural women breadwinners, Using a questionnaire by personal interview during November and December 2021, analyze data used Frequencies, percentages, means, weighted Mean, standard deviation, Alpha coefficient, Pearson correlation, "Pearson" correlation coefficient, multiple correlation coefficient and partial regression. 82.8% of respondents have a medium level from quality of life, While The level of benefit from development efforts was concentrated in the medium and low levels, Half of the respondents in high level From Exposure to problems, Economic problems ranked first, There is a positive significant correlation between the quality of life of the respondents and each of: years of education, monthly income, degree of satisfaction with development projects, benefit from economic, educational and extension, political, and benefit from social development efforts, A negative and significant correlation between:age, exposure to economic, health, and social problems.
Keywords: development efforts; breadwinner women; quality of life